TRANSFORMATIVE PHASES OF SPIRITUAL PROGRESS IN ‘DASĀVATĀRA’ (TEN INCARNATIONS) - Rao, Y. V. Subba (International Journal of Research -GRANTHAALAYAH, 2022)
The ‘Dasāvatāra’ (Ten Incarnations) of Lord Vishnu that came to eradicate wicked forces of adharma (wickedness) and restore dharma (righteousness) shows different stages of man’s evolution from aquatic life to invertebrates, vertebrates, to modern man and finally liberation of soul all by merit. The causes and processes behind the physical evolution were not deliberated in Indic philosophy where the common ancestor is Brahma. Origin of life of all species is extra-terrestrial of lower frequencies to higher frequencies occurs automatically with each rebirth until human birth while evolution and proliferation of life of all species is only on the earth. There is no life in physical form anywhere else in the cosmos save on this planet. where life in other higher worlds exist in astral form. The ‘Dasāvatāra’ (Ten Incarnations) of Lord Vishnu reflects transformative phases of spiritual progress where an ordinary person disciplines himself to evolve as a spiritually evolved person bordering on divinity and obtain liberation or ‘moksha’. The notion of 'Dasvatra' is seen to resemble Charles Darwin's theory of evolution in several ways. The first incarnation of Vishnu as a fish resembles the Silurian Period's evolutionary origin of fish. The Geological Time Scale's history of events corresponds to the Vedic timeline of ten incarnations. The first explanation of physical evolution was given by Hinduism much before Charles Darwin did.